Sentinel Node Microscopic Metastasis Detected after Segmentectomy for Lung Cancer Followed by Completion Lobectomy: Two Case Reports - Fukutomi, T.; Kohno, M.; Izumi, Y.; Hayashi, Y.; Nakahara, T.; Nomori, H. (The Thoracic and Cardiovascular Surgeon, 2012)
We performed sentinel node identification using radioisotopic and/or dye techniques to determine the final indication after segmentectomy in cases with non-small cell lung cancer. Sentinel nodes were examined using intraoperative frozen sections stained with hematoxylin and eosin. We present 2 cases with completion lobectomy performed 7 and 11 days after segmentectomy because immunohistochemical staining of the sentinel nodes showed the presence of microscopic metastases that were not detected by the examination of intraoperative frozen sections.
Keywords: lung cancer treatment (surgery, medical); lung cancer; diagnosis (includes staging, imaging, fiducials); metastases; non-small cell lung cancer; sentinel node; segmentectomy; micrometastasis